2017
DOI: 10.1177/1077801217731542
|View full text |Cite
|
Sign up to set email alerts
|

Using the Woman Abuse Screening Tool to Screen for and Assess Dating Violence in College Students

Abstract: The study aimed to evaluate the measurement properties of the Woman Abuse Screening Tool (WAST) in Chinese college students. A cross-sectional survey was conducted in Hong Kong. A cutoff score of 10 was found to be able to discriminate between abused and nonabused Chinese young adults. The total score was significantly correlated with total scores for anxiety and depression on the Chinese version of the Hospital Anxiety and Depression Scale. Two-factor structure of the WAST was supported by exploratory and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, the data did not fit either of these models. Consequently, the data were split into training (n = 250) and test (n = 250) sets [29]. The training set was used in an exploratory factor analysis (EFA) using principal axis factoring with promax rotation of factors with eigenvalues of > 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data did not fit either of these models. Consequently, the data were split into training (n = 250) and test (n = 250) sets [29]. The training set was used in an exploratory factor analysis (EFA) using principal axis factoring with promax rotation of factors with eigenvalues of > 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…Following rigorous procedures for cultural adaptation, studies from Hong Kong translated and validated Chinese versions of several instruments measuring and/or screening for IPV, including the Abuse Assessment Screen (AAS) [81] , the Extended-Hurt, Insult, Threaten, Scream (E-HITS) [82] , the Revised Controlling Behaviors Scale (CBS-R) [83] , the Psychological Maltreatment of Women Inventory (PMWI) [84] , the Woman Abuse Screening Tool (WAST) [85] , and the Scale of Economic Abuse-12 (SEA-12) [86] . These validated instruments demonstrated satisfactory psychometric properties among Chinese population in Hong Kong; but they were not able to be directly used among Chinese population in mainland China, with the difference in Chinese characters in the two regions serving as one of the most obvious reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, screening of dating violence not only encompasses the identification of warning signs but also requires that providers carefully analyze each indicator ( Wong et al, 2018 ), because a combination of indicators might be a sign that another problem is occurring. Researchers consistently have concluded that dating violence among college students is correlated to other health concerns, such as drug and alcohol abuse and risky sexual behaviors ( Duval et al, 2020 ; Sabina et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%